Filling the gap : - Norlund, Irene (Ministry of Culture and Information of S.R. Viet Nam, 2007)
The dícision paper is intended to contribute to the policy dialogue in civil society development among donor agenciesa and between donors and the government of Viet Nam. The discussion paper is divided into 5 sections: a brief analysis of recent socio-economic and political trends in VN, the outline of the CSI study in VN, findings and conclusions form the CSI study's 4 dimensions, the conclusions from the CSI study and some recommendations on how the sector can be strenthened in VN.